2021
DOI: 10.22331/q-2021-12-28-612
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-protected sign problem and magic in quantum phases of matter

Abstract: We introduce the concepts of a symmetry-protected sign problem and symmetry-protected magic to study the complexity of symmetry-protected topological (SPT) phases of matter. In particular, we say a state has a symmetry-protected sign problem or symmetry-protected magic, if finite-depth quantum circuits composed of symmetric gates are unable to transform the state into a non-negative real wave function or stabilizer state, respectively. We prove that states belonging to certain SPT phases have these properties,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 94 publications
(210 reference statements)
0
7
0
Order By: Relevance
“…There is some equivocation on terminology here: in particular, the definition of "long-range magic" in[55] differs from the definition in this paper.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…There is some equivocation on terminology here: in particular, the definition of "long-range magic" in[55] differs from the definition in this paper.…”
mentioning
confidence: 83%
“…It is an open question if there is a suitable linear combination of magic monotones to unambiguously detect long-range magic (akin to the Kitaev-Preskill/Levin-Wen measure of long-range entanglement [53,54]), in more physically relevant systems, however very recent work indicates that "long-range magic" 17 is a useful diagnostic of symmetry protected and many body phases [55,56]. Developing continuum effective field theory descriptions of these investigations is an interesting avenue for future research.…”
Section: Diagnosing Topologically Insulating Phasesmentioning
confidence: 99%
“…As a, b can be arbitrarily far apart, the MIE does not decay. This is the "quantum wire" property of 1d SPTs [13], a manifestation of a symmetry-protected sign problem in the symmetry charge (Z) basis [10].…”
Section: A Bound On Mie For Sign-free Stabilizer Statesmentioning
confidence: 99%
“…In Ref. [10], it was shown that many symmetry-protected topological (SPT) phases have a symmetry-protected sign problem, which no symmetric finite depth circuit can remove. Moreover, the sign structure of highly excited and random states is intimately connected to their volume law entanglement scaling [11].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, numerical approaches that can handle the large system sizes needed for exploring quantum criticality require a sign-problem-free realization. Indeed, certain phases are known to have an intrinsic sign problem [55][56][57][58]. Secondly, in the absence of large continuous symmetry groups, direct continuous transitions are often interrupted by direct first order transitions or intervened by intermediate phases [59][60][61] (which can nevertheless be exotic such as the gapless stripe phase reported in Ref.…”
Section: Introductionmentioning
confidence: 99%